Effectiveness of PHBS Pocketbook as Intervention Media for Elementary School Students - Humairo, Mika Vernicia; Sukarno Putri, Paramytha Magdalena; Ulfah, Nurnaningsih Herya; ,, Ainna Salima; Nafisah, Azalia Fakhirotul; Lasmunifa, Sarah Sabrina Putri; Syawanah, Aquila Dzikri (Universitas Padjadjaran, 2026)
Clean and Healthy Living Behavior (PHBS) is an important effort to improve the health quality of elementary school students. This community service activity aims to improve the knowledge and behavior of PHBS students of SDN Sumbersari 03 Malang through the media of the pocket book